Mechanochemistry and mechanical properties of carbon nanotubes: Advances in experimental, theoretical, and computational understanding - Tiwari, Mijas (Himalayan Physics, 2025)
This comprehensive review examines the mechanochemistry and mechanical properties of carbon nanotubes (CNTs) through integrated analysis of experimental and theoretical research. Experimental studies reveal exceptional mechanical characteristics including Young's moduli up to 1.8 TPa, tensile strengths exceeding 100 GPa, and unique deformation mechanisms like reversible buckling and "sword-in-sheath" fracture. Theoretical frameworks establish structure-property relationships, demonstrating how Stone-Wales defects, chirality, and functionalization govern mechanical behavior at atomic scales. Cross-validation shows remarkable alignment between atomistic simulations and empirical measurements, particularly for elastic moduli and defect-mediated failure. Modern approaches employing irradiation-induced crosslinking and machine learning demonstrate significant enhancements in load transfer efficiency and property prediction accuracy. Critical research gaps persist in understanding chirality-specific fracture dynamics and scalable composite integration, while emerging techniques combining machine learning with multiscale modeling offer promising pathways for predictive nanomaterial design. This synthesis provides fundamental insights for advancing CNT-based applications in high-performance composites and nanoelectromechanical systems.